Utilization of Crumb Rubber as Additive in Asphalt Concrete for Sustainable Road Construction - ADENAN, NUR SYADIYA; Syed Mohd Fareed, (Progress in Engineering Application and Technology, 2025)
This study investigates the use of crumb rubber as an additive in modified asphalt concrete to enhance pavement performance and sustainability. Rutting, caused by repeated traffic loads and high temperatures, significantly impacts the lifespan and durability of asphalt pavements. The research examines the physical properties of crumb rubber-modified asphalt, with a focus on determining the optimal particle size and evaluating its performance under different loading and environmental conditions. Crumb rubber sizes of 2.36mm, 1.18mm, 0.425mm, and 0.075mm were incorporated into the asphalt mix for analysis. Results indicated that crumb rubber with a particle size of 0.075mm exhibited superior performance, attributed to its larger surface area, which allowed better bonding with the bitumen binder. Performance tests such as Marshall Stability, Marshall Flow, and stiffness evaluations identified 0.075mm as the optimal size, enhancing elasticity, stiffness, and deformation resistance. Durability tests under wet conditions showed that larger particle sizes (2.36mm and 1.18mm) provided better void filling but resulted in lower performance compared to 0.075mm. These findings demonstrate the potential of crumb rubber as a sustainable additive in asphalt concrete, improving mechanical properties and contributing to the recycling of waste materials for road construction.